Adaptive clinical trials: overview 1 - Shyr, Yu (Henry Stewart Talks, 2017)
Definition of an adaptive clinical trial, FDA: guidance for adaptive design clinical trials, Frequentist vs. Bayesian vs. likelihood, Three major branches of the statistics, Example of an adaptive clinical trials design, Two-stage designs, Revised design, Simon two-stage design, Balanced design, Gehan and Fleming two-stage design